Evolution of Treatment Outcomes and Prognostic Factors in Esophageal Cancer Surgery: A Retrospective Analysis of 1500 Consecutive Esophagostomies - Yasue Kimura, MD, PhD; Eiji Oki, MD, PhD; Tomonori Nakanoko, MD, PhD; Qingjiang Hu, MD, PhD; Keita Natsugoe, MD; Sho Nanbara, MD, PhD; Ryota Nakanishi, MD, PhD; Yuichiro Nakashima, MD, PhD; Mitsuhiko Ota, MD, PhD; Tomoharu Yoshizumi, MD, PhD (Annals of Surgery Open)
Objective:. To clarify the surgical outcomes of esophagectomy in Japan and comprehensively evaluate trends over time. It is important to analyze data from a large number of consecutive patients from a single institution. Methods:. We evaluated the treatment outcomes, complications, and prognosis of 1500 consecutive patients who underwent esophagectomy during 5 periods: group A (n = 284), 1964–1984; group B (n = 345), 1985–1993; group C (n = 253), 1994–2002; group D (n = 297), 2003–2012; and group E (n = 321), 2013–March 2020. Results:. The incidences of squamous cell carcinoma and adenocarcinoma were 93.8% and 3.3%, respectively. The proportion of adenocarcinoma cases has gradually increased over time. The in-hospital mortality rates for groups A, B, C, D, and E were 12%, 4.6%, 1.2%, 2.9%, and 1.5%, respectively. Group A had a significantly higher mortality rate than the other groups (P < 0.0001). Three-year survival rates were 22.2%, 47.8%, 53.4%, 69.9%, and 72.6% in groups A–E, respectively, 5-year survival rates were 17.2%, 41.3%, 49.2%, 63.9%, and 68.4%, respectively (P < 0.0001, group A vs groups D and E). The prognosis improved over time. Multivariate analysis revealed that depth of invasion, lymph node metastasis, the extent of lymph node resection, curative resection, pulmonary complications, and anastomotic leakage were significant independent prognostic factors. However, for recent surgeries (groups D and E), only the depth of invasion, lymph node metastasis, and curative resection were significant independent prognostic factors. Conclusions:. Valuable changes in background and prognostic factors occurred over time. These findings will help optimize esophageal cancer management and improve patient outcomes.